PENERAPAN ISLAMIC MONTESSORI ACTIVITY PADA KEGIATAN PEMBELAJARAN ANAK USIA DINI DI RA TUNAS MULIA DUA DESA PANDANLANDUNG KECAMATAN WAGIR KABUPATEN MALANG - Nency Ucik Kusnawati; Anwar Sa’dullah; Eko Setiawan (Jurnal Dewantara, 2021)
Montessori method is an educational method that emphasizes the concept of playing while learning and learning to be. RA Tunas Mulia Dua applies Montessori method which is integrated with Islamic understanding or Islamic Montessori Activity. Formulating the problem in this study is how the application of Islamic Montessori Activity on learning, impacts and factors that support and inhibit it. The purpose of this study is to identify its application, impact and supporting and inhibitory factors. This type of research uses qualitative approach in the form of case studies. Data collection procedures are carried out by means of observation, interviews and documentation. The results of the study of the application of Islamic Montessori Activity in RA Tunas Mulia Dua can be found in the lesson plan implemented in seven areas of Montessori namely Islamic studies, practical life, sensorial, language, mathematic, culture, art &carf. The props used are the creations of teachers and guardians. Every activity in learning is always associated with the understanding of Islam.